2008
DOI: 10.1128/jb.01447-07
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the yjjQ - bglJ Operon, Encoding LuxR-Type Transcription Factors, and the Divergent yjjP Gene by H-NS and LeuO

Abstract: The yjjQ and bglJ genes encode LuxR-type transcription factors conserved in several enterobacterial species. YjjQ is a potential virulence factor in avian pathogenic Escherichia coli. BglJ counteracts the silencing of the bgl (␤-glucoside) operon by H-NS in E. coli K-12. Here we show that yjjQ and bglJ form an operon carried by E. coli K-12, whose expression is repressed by the histone-like nucleoid structuring (H-NS) protein. The LysR-type transcription factor LeuO counteracts this repression. Furthermore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 59 publications
(92 reference statements)
4
73
0
Order By: Relevance
“…Further, the RcsA protein is a substrate of the ATP-dependent Lon protease, which adds a further level of control on RcsA (14). The bglJ gene is the second gene of the H-NS repressed yjjQ-bglJ operon that can be activated by the pleiotropic transcription regulator LeuO (54). However, the leuO gene is also repressed by H-NS at standard laboratory growth conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the RcsA protein is a substrate of the ATP-dependent Lon protease, which adds a further level of control on RcsA (14). The bglJ gene is the second gene of the H-NS repressed yjjQ-bglJ operon that can be activated by the pleiotropic transcription regulator LeuO (54). However, the leuO gene is also repressed by H-NS at standard laboratory growth conditions.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main elements in this control is the availability of the interaction partners. Expression of all of the corresponding genes is repressed by the nucleoid-associated and global repressor protein H-NS (22,47,54,55) (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…This effect would be overcome by V. cholerae regulatory proteins that, under appropriate environmental conditions, could act as antirepressors to alleviate the effects of H-NS on tcp and ctx expression. Indeed, several bacterial regulatory proteins are known to alleviate H-NS repression by displacing H-NS from the DNA (8,38,61,63). At the tcpA promoter we have previously reported that both ToxT and IHF act as antirepressors of H-NS (60).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a single protein may counter silencing by more than one mechanism. The LysR family regulator LeuO counters H-NS silencing of the putative virulence gene yjjQ in avian pathogenic E. coli [52] and H-NS/StpA silencing of the ompS1 porin gene in Salmonella [53]. The importance of H-NS in regulating horizontal gene transfer is not limited to pathogenesis.…”
Section: Counter-silencing Of H-ns and Its Functional Consequencesmentioning
confidence: 99%